Tracking KLRC2 (NKG2C)+ memory-like NK cells in SIV+ and rhCMV+ rhesus macaques. - Daniel R Ram; Cordelia Manickam; Brady Hueber; Hannah L Itell; Sallie R Permar; Valerie Varner; R Keith Reeves (PLoS Pathogens, 2018)
Natural killer (NK) cells classically typify the nonspecific effector arm of the innate immune system, but have recently been shown to possess memory-like properties against multiple viral infections, most notably CMV. Expression of the activating receptor NKG2C is elevated on human NK cells in response to infection with CMV as well as HIV, and may delineate cells with memory and memory-like functions. A better understanding of how NKG2C+ NK cells specifically respond to these pathogens could be significantly advanced using nonhuman primate (NHP) models but, to date, it has not been possible to distinguish NKG2C from its inhibitory counterpart, NKG2A, in NHP because of unfaithful antibody cross-reactivity. Using novel RNA-based flow cytometry, we identify for the first time true memory NKG2C+ NK cells in NHP by gene expression (KLRC2), and show that these cells have elevated frequencies and diversify their functional repertoire specifically in response to rhCMV and SIV infections.